Morphometric characterization of a large scale rockslide, and probable seismogenic origin of landslides on the western flank of Central Precordillera, Argentina - Esper Angillieri, Maria Yanina (2014)
The distribution of late Pleistocene to Holocene rockslides in the western flank of the eastern mountain ranges of Central Precordillera (30° 40′–31° S), has been analyzed to determine the triggering mechanisms. The mode of failure was determined to be translational sliding. This paper presents the results of research on one of the Holocene rockslides located in the western flank of Sierra de La Dehesa, which is composed of stratified limestones of early Paleozoic age. In order to characterize this slide, high resolution satellite imagery interpretation was carried out, along with the recognition of the landslide detachment zones and landslide bodies with the aim of reconstructing the pre-slide topography. The model proposed for this slide is a translational or planar slide, as the mode of failure was along a broadly planar surface accompanied by shear or tensile fractures and joints. The estimated rock volume involved is 1.24 Mm3. We compared rockslide occurrence patterns to slope, topography, lithology, geological structures, and seismicity records. After analysis of the spatial relationships among all the slides and the distribution of seismic epicenters, historical earthquakes and neighboring Quaternary faults as seismogenic sources, we hypothesize that these Quaternary rockslides in the Central Precordillera have been triggered by shallow seismicity associated with active faults.